Síntese de polímeros supramoleculares derivados dos ácidos palmítico e mirístico com meglumina e suas caracterizações em meio aquoso - Lopes Junior, Marco Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Currently many researchers have turned their attention to the field of supramolecular chemistry, a relatively new area of chemistry that works with the compounds beyond the atoms, beyond a single molecule, works with the intermolecular interactions, such as van der Waals bonding, hydrophobic interaction, dipole dipole bonding and hydrogen bonding. The studies in this area, especially on supramolecular polymers can propose new techniques for the synthesis of various compounds such as elastomers, supramolecular gels, thermotropic liquid crystals, superhydrophobic surfaces, giant micelles, and many other materials examples. This dissertation demonstrates a simple technique for the synthesis of supramolecular compounds intermolecular interactions formed by self-assembly, using two different carboxylic acids (myristic acid that have fourteen carbons in their structure and palmitic acid that have sixteen carbons in its structure) and the meglumine. Then establish a relationship of carbon chain of the size difference of the acid with the possible formation of supramolecular compounds. The characterization of the compounds was obtained by techniques such as thermogravimetry (TG-DTG), differential scanning calorimetry (DSC), nuclear magnetic resonance (NMR), relative viscosity, calculation of surface tension and the consequent obtaining of the critical aggregation concentration. It was possible to observe the formation of carboxylate-meglumine adducts, the supramolecular polymerization of the compound palmitate-meglumine when in aqueous solution with a concentration above 2% (w/w) and the non-polymerization of myristate-meglumine compound, even at high concentrations such as 50% (w/w). Was also observed that the temperature required to cause the gel-sol transition on the supramolecular polymer palmitate-meglumine in aqueous solution 6% (w/w) is relatively low, around 37.58 ºC.

Atualmente muitos pesquisadores tem voltado sua atenção para a área da química supramolecular, uma área relativamente nova da química que estuda os compostos além dos átomos, além de uma única molécula, estuda as interações intermoleculares, tais como ligação de van der Waals, interação hidrofóbica, ligação dipolo-dipolo e ligação de hidrogênio. Os estudos nesta área, principalmente sobre polímeros supramoleculares podem propor novas técnicas para a síntese de diversos compostos como elastômeros, géis supramoleculares, cristais líquidos termotrópicos, superfícies super-hidrofóbicas, micelas gigantes, entre diversos outros exemplos de materiais. Esta dissertação demonstra uma técnica simples para síntese de compostos supramoleculares com interações intermoleculares formados por auto-montagem, utilizando para isso dois ácidos carboxílicos (o ácido tetradecanóico (C14:0) e o ácido hexadecanóico (C16:0)) e a meglumina, podendo assim estabelecer uma relação da diferença do tamanho da cadeia carbônica dos ácidos com a possível formação de compostos supramoleculares. Foi feita a caracterização dos compostos obtidos por meio de técnicas como termogravimetria (TG-DTG), calorimetria exploratória diferencial (DSC), ressonância magnética nuclear (RMN), viscosidade relativa, cálculo da tensão superficial e consequente obtenção da concentração de agregação crítica, podendo assim observar a formação dos adutos carboxilato-meglumina, a polimerização supramolecular do composto palmitato-meglumina quando em solução aquosa com concentração acima de 2% (m/m) e a não polimerização do composto miristato-meglumina mesmo em concentrações elevadas como 50% (m/m). Também foi observado que a temperatura necessária para que ocorra a transição gel-sol do polímero supramolecular palmitato de meglumina em solução aquosa 6% (m/m) é relativamente baixa...
Keywords: Química supramolecular; Forças intermoleculares; Polímeros; Ácidos graxos; Tensão superficial; Fatty acids